DYNAMICS OF IMMUNOLOGICAL INDICATORS IN THERAPY OF EXPERIMENTAL TOXIC HEPATITIS IN RATS WITH SAFFLOWER OIL - Faizullaeva N. Ya.; Kayumov A. A.; Raufov A. A. (Web of Journals Publishing, 2025)
This study assessed the effects of safflower oil on cytokine dynamics, angiogenesis factors, and metabolic regulators in an experimental rat model of toxic hepatitis. IL-1β levels were 1.47-fold higher on day 7 and 2.04-fold higher on day 14 compared to intact animals (p<0.05), indicating reduced inflammatory activity. IL-4 concentration exceeded control values 2.19- and 2.06-fold on days 7 and 14, respectively (p<0.05), reflecting stimulation of regenerative processes. IL-6 showed a 1.34-fold and 1.56-fold increase (p<0.05), while TNFα rose 2.12- and 2.59-fold (p<0.05), demonstrating immune activation. VEGF-A levels increased 3.63-fold on day 7 and 2.54-fold on day 14 (p<0.05), confirming angiogenesis induction. βKlotho levels were 4.47-fold and 2.14-fold higher on days 7 and 14 (p<0.05), indicating prolonged cytoprotective effects. These findings confirm the strong immunomodulatory and hepatoprotective potential of safflower oil, mediated through cytokine modulation and enhanced regenerative mechanisms.
Keywords: Toxic hepatitis, safflower oil, cytokines, immune response, VEGF-A, βKlotho.